MENINGKATKAN KEMAMPUAN VISUAL PERSEPTUAL ANAK USIA 5-6 TAHUN MELALUI PEMBELAJARAN BERBASIS SMARTBOARD DI TK SARANTAU SASURAMBI - Monica Sikma; Rio Tri Putra; Sri Suhartika; Ade Marlia (PT. Jurnal Center Indonesia Publisher, 2025)
Visual perceptual ability is one of the important aspects of cognitive development in early childhood. This ability is related to children’s capacity to recognize, differentiate, interpret, and understand information received through vision. It includes the recognition of shapes, colors, sizes, patterns, and visual relationships, which are essential for children’s learning readiness. This study aims to improve the visual perceptual abilities of children aged 5–6 years at TK Sarantau Sasurambi through smartboard-based learning. The research employed a Classroom Action Research (CAR) method conducted in several cycles, namely planning, action, observation, and reflection. The research subjects were children aged 5–6 years. The research instruments included observation sheets of visual perceptual abilities (visual discrimination, visual memory, matching, sequencing, spatial relations, and eye–hand coordination), observation sheets on the use of the smartboard, and field notes. The results showed an improvement in visual perceptual abilities from the pre-cycle to Cycle I and Cycle II. Children’s mastery in the pre-cycle reached only 45%, increased to 65% in Cycle I, and reached 88% in Cycle II. The use of smartboards proved effective as it offers interactive and engaging visual learning experiences and facilitates children’s direct manipulation of objects. Therefore, smartboard-based learning is highly effective in improving the visual perceptual abilities of children aged 5–6 years.